MENGEMBANGKAN KELOMPOK MENJAHIT BINTAN BERKARYA MELALUI KERAJINAN TANJAK SEBAGAI WARISAN BUDAYA MELAYU - Pardede, Ranat Mulia; Sihombing, Agustinus; Yanto, Meidi; Syahputra, Ilham Kurniawan; Setiawan, Roni; Malinda, Delsa; Cahayani, Nur Suci; Anugrah, Sentia; Pratiwi, Erica (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
In Ekang Anculai Village, there is a group that manages MSMEs engaged in sewing which are members of a group called "Bintan Berkarya". The "Bintan Berkarya" sewing group is a forum for introducing, developing, and preserving the dance culture, especially in the Bintan area and its surroundings by providing an understanding both educationally and practically so that the dances produced have indicators of success. November 12, 2022 at the Ekang Anculai Village Hall with the sewing group "Bintan Berkarya" as the participant. Equipment and tools for making climbing products were provided by students who were doing KKN in Ekang Anculai Village as the implementing committee for this climbing training activity. During the training, the entire team was able to work well together and provide equipment to support the ongoing management of the treads by the "Bintan Berkarya" sewing group